OPTIMIZING THE ROLE OF COMMUNITY SELF-HELP GROUP INUTILIZING NEW MEDIA AS A PROMOTIONAL TOOL for THE POTENTIAL OF THE VILLAGE IN JALANCAGAK DISTRICT, SUBANG REGENCY - Affandi, Nur Ratih Devi; Fitrananda, Charisma Asri (LPM Universitas Pasundan, 2023)
The potential of a village, including its natural resources and human resources, can be harnessed and developed into a tourist village in various sectors such as economics, education, social, and environment. The development of village potential involves the collaboration between the community and the government, with Jalancagak District in Subang Regency being one of the locations that has diverse village potential, such as tea plantations, waterfalls, amusement parks, and hot springs. To optimize the village potential, the involvement of Community Self-Help Groups (KSM) is crucial. KSM is a solidarity movement organization that focuses on socioeconomic development through community empowerment. In order to enhance the performance and capacity of KSM, mentoring from partners is necessary, particularly in promoting the village potential using new media to overcome partner-related issues. The purpose of this Community Service (PKM) activity is to stimulate partners in determining strategies for utilizing new media, conducting promotions in forums, using hashtag strategies, implementing SEO, involving influencers, and leveraging special moments. The methods used include analyzing the potential issues in the village, providing guidance on new media and its utilization, mentoring the creation of effective village promotional content, and creating promotional content on various new media platforms such as Instagram, YouTube, and TikTok with direct involvement of KSM.The conclusion of this activity indicates that the stimulation, materials, and direct mentoring provided are engaging and eagerly anticipated, providing KSM members with a platform to explore and promote the village potential using new media. Keywords: The potential of village, Community Self-Help Groups, New Media